Real‐Time Analytic Antialiased Text for 3‐D Environments. (14th November 2019) - Ellis, A.; Hunt, W.; Hart, J.
Abstract: Text is a crucial component of 3‐D environments and virtual worlds for user interfaces and wayfinding. Implementing text using standard antialiased texture mapping leads to blurry and illegible writing which hinders usability and navigation. While super‐sampling removes some of these artifacts, distracting artifacts can still impede legibility, especially for recent high‐resolution head‐mounted displays. We propose an analytic antialiasing technique that efficiently computes the coverage of text glyphs, over pixel footprints, designed to run at real‐time rates. It decomposes glyphs into piecewise‐biquadratics and trapezoids that can be quickly area‐integrated over a pixel footprint to provide crisp legible antialiased text, even when mapped onto an arbitrary surface in a 3‐D virtual environment.